1970
DOI: 10.1037/h0029003
|View full text |Cite
|
Sign up to set email alerts
|

Mathematicians: The creative researcher and the average PhD.

Abstract: A sample of 60 mathematicians is shown to differ from scientists in demographic and personality characteristics. Creative 5s were more flexible and richer in personality than comparison 5s, though not higher in personal ascendance or in IQ. They were more often the eldest child in their family and described their mothers with more respect and warmth. They came from higher socioeconomic backgrounds, but the native-born creatives came from less privileged backgrounds than have been reported for eminent scientist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 15 publications
1
37
1
3
Order By: Relevance
“…Numerous individual-difference variables appear to separate those who merely master domain-specific skills and knowledge from those who actually make creative contributions (Feist, 1998;Simonton, 1999a;Sternberg & Lubart, 1995). For example, many personality studies have indicated that those who are considered notable creators in a domain have identifiably different character traits than do domain experts (i.e., persons who are otherwise comparable in training, experience, and professional standing; see, e.g., Barron, 1969;Helson & Crutchfield, 1970;MacKinnon, 1978;Rostan, 1994). Among the distinguishing attributes are the creator's greater inclination toward nonconformity, unconventionality, independence, openness to experience, ego strength, aggressiveness, risk taking, introversion, and even psychopathology.…”
Section: Empirical Problems With the Creative-expertise Hypothesismentioning
confidence: 99%
“…Numerous individual-difference variables appear to separate those who merely master domain-specific skills and knowledge from those who actually make creative contributions (Feist, 1998;Simonton, 1999a;Sternberg & Lubart, 1995). For example, many personality studies have indicated that those who are considered notable creators in a domain have identifiably different character traits than do domain experts (i.e., persons who are otherwise comparable in training, experience, and professional standing; see, e.g., Barron, 1969;Helson & Crutchfield, 1970;MacKinnon, 1978;Rostan, 1994). Among the distinguishing attributes are the creator's greater inclination toward nonconformity, unconventionality, independence, openness to experience, ego strength, aggressiveness, risk taking, introversion, and even psychopathology.…”
Section: Empirical Problems With the Creative-expertise Hypothesismentioning
confidence: 99%
“…Perhaps the best illustration of this tradition is the research conducted at the Institute of Personality Assessment and Research (IPAR) 2 at the University of California, Berkeley. Eminent architects, scientists, and creative writers were invited to IPAR (along with control groups of less illustrious colleagues), where they were subjected to a rich array of assessment techniques, including interviews and psychological tests (e.g., Barren, 1969;Dudek & Hall, 1984;Helson & Crutchfield, 1970).…”
Section: Four Research Traditionsmentioning
confidence: 99%
“…Barron (1963) and Bergum (1975) have made similar observations. Helson and Crutchfield (1970) administered the California Psychological Inventory to 105 mathematicians who had been rated for creativity by other mathematicians. The more creative mathematicians scored significantly higher on the flexibility scale than did the less creative mathematicians.…”
Section: The Drive For Originalitymentioning
confidence: 99%